Multilocus Sequence Typing (MLST) Genotypes of Candida glabrata Bloodstream Isolates in Korea: Association With Antifungal Resistance, Mutations in Mismatch Repair Gene (Msh2), and Clinical Outcomes - Byun, Seung A.; Won, Eun Jeong; Kim, Mi-Na; Lee, Wee Gyo; Lee, Kyungwon; Lee, Hye Soo; Uh, Young; Healey, Kelley R.; Perlin, David S.; Choi, Min Ji; Kim, Soo Hyun; Shin, Jong Hee (Frontiers in Microbiology, 2018)
Candida glabrata bloodstream infection (BSI) isolates from a particular geographic area have been reported to comprise a relatively small number of the major sequence types (STs) by multilocus sequence typing (MLST) analysis. Yet little it known about the characteristics of major ST strains of C. glabrata. To address this question in Korea, we investigated antifungal resistance and nonsynonymous mutations of the mismatch repair gene (msh2 mutations) in C. glabrata BSI isolates, as well as associated clinical characteristics, and compared the results according to MLST genotype. We assessed a total of 209 C. glabrata BSI isolates from seven hospitals in Korea for two years (2009 and 2014). Clinical features of candidemia and their outcomes were analyzed for 185 available cases. According to MLST, ST7 (47.8%) was the most common type, followed by ST3 (22.5%); the remainder represented 28 types of minor STs (29.7%). Fluconazole-resistance (FR) rates for ST7, ST3, and other strains were 9.0% (9/100), 8.5% (4/47), and 4.8% (3/62), respectively, and all were susceptible to amphotericin B and micafungin. All ST7 isolates harbored the V239L mutation in msh2, known to confer hypermutability, while 91.5% of ST3 isolates did not harbor the msh2 mutation. Overall, isolates of the same ST had identical msh2 mutations, with the exception of nine isolates. The msh2 mutations were identified in 68.8% (11/16) of the FR isolates and 67.4% (130/193) of the fluconazole susceptible-dose dependent isolates. There was no significant difference in all clinical characteristics between ST3 and ST7. However, the 30-day mortality of C. glabrata candidemia due to the two major ST (ST3 or ST7) strains was significantly higher than that of candidemia due to other minor ST strains (45.1% vs. 25.0%, p < 0.05). Multivariate logistic regression analysis also showed that two major STs (ST3 and ST7) were independent predictors of 30-day mortality. This study showed for the first time that two STs (ST7 and ST3) were predominant among BSI isolates in Korea, and that C. glabrata BSI isolates belonging to two major MLST genotypes are characterized by higher mortality. In addition, most msh2 mutations align with MLST genotype, irrespective of FR.